PERFORMANCE PRODUCTION AND CHARACTERISTIC CARCASS OF JOPER CHICK THAT OFFERED ADDITIVE EXTRACT OF Carica papaya L LEAF - SRIYANI, N. L. P.; WIRAPARTHA, M.; DEWI, G. A. M. K. (Majalah Ilmiah Peternakan; Vol 26 No 3 (2023): Vol. 26 No. 3 (2023)DO - 10.24843/MIP.2023.v26.i03.p06, 2024)
The objective of this research is to know the performance of the production and carcass characteristic of Joper chick that offered additive extract of the Carica Papaya L leaf in it drinking water. The research used Complete Randomized Design with 4 treatments and 4 replicates. The animal used were 48 Jover chicks. Each replicate was consisted of 3 chicks. The treatments were P0 (drinking water without additive extract of the Carica Papaya L leaf; P1 (drinking water plus 25 ml of additive extract of the Carica Papaya L leaf; P2 (drinking. water plus 30 ml of additive extract of the Carica Papaya L leaf; P3 (drinking water plus 35 ml of additive extract of the Carica Papa- ya L leaf. Variable that were observed were production performance i.e. body weight, feed consumption and Feed Conversion Ratio (FCR) and carcass characteristic i.e. carcass weight, carcass percetage, comercial carcass cut. Data were analized use one way analysis variance, and if there is significant different (P < 0,05) it will be continued use Duncan test. Results of the research showed that there was no significant different on performance variable of production i.e. end of body weight, body weight gain, and feed consumption except variable of FCR of the P3 was the lowest and significant different (P < 0.05) than the others. This result showed that the P3(drinking water plus 35 ml extract of the Carica Papaya L leaf ) could increased feed intake efficiency of the chick. The research was also showed that the addition of extract of the Carica Papaya L leaf in the drinking water was no significantly affected to the carcass characteristic of the chicks.